Exploring Student Attention in Junior High School Classrooms: A Case Study at SMPN 19 Surabaya - Raniadi, Divani; Hanafi, M.; Adriana, Dina (Universitas Sang Bumi Ruwa Jurai, 2025)
Attention of students is an important aspect of effective learning since it directly determines comprehension, memory and classroom participation. But focus is also an issue as it is easy to lose track with distractions, mental exhaustion and the repetitive ways of teaching. The purpose of this study was to determine the causes of inattention among 7th grade students of SMP Negeri 19 Surabaya in the 2024-2025 academic year. A sample of 33 students was used through completion of questionnaires and five students were used in semi-structured interviews to learn more about their lived experiences. The thematic analysis showed that the lapses of attention were not consistent but were always situational, with noisy peers, lack of clarity when explaining the concepts to the students, and fatigue being the most prevalent reasons. Students used to deal with losing focus by doodling, chatting or switching seats or making personal notes. The results show that the attention depends not only on the internal state of students but also on the classroom ecology and the quality of instruction. In theory, this research expands the knowledge on the maintenance of attention by autonomy-supportive environments. In practice, it implies that educators can make their classes more focused by incorporating interactive instruction, gamified learning, and brief brain-break exercises to establish dynamic and psychologically supportive learning environments.